2018
DOI: 10.21829/azm.2018.3412159
|View full text |Cite
|
Sign up to set email alerts
|

Nuevos registros de arañas (Arachnida: Araneae) para la Región del Cabo, península de Baja California, México

Abstract: Se dan a conocer 11 nuevos registros de arañas para la Región del Cabo, península de Baja California. Dos son nuevos registros para México (Tennesseellum gollum y Araneus illaudatus); dos géneros (Edricus y Pozonia) y siete especies son nuevos registros para Baja California Sur (Eustala emertoni, Arctosa minuta, Frontinella pyramitela, Chrysso albomaculata, Ariamnes mexicanus, Neospintharus baboquivari y Xysticus californicus). Se reconfirma a Phioponella arizonica para esta región. Se discute la distribución … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…Most of the Mexican species were described or recorded from the end of the 19 th century to the first half of the 20 th century (Banks 1898;Pickard-Cambridge 1902;Gertsch & Davis 1937, 1946 and later, only two publications by Millidge (1983Millidge ( , 1987 added another important number of species. Since then, only five species have been added to the Mexican Linyphiidae fauna (Ibarra-Núñez et al 2011;Prentice & Redak 2013;Gómez-Rodríguez et al 2014;Jiménez et al 2018;Campuzano Granados et al 2019). The discovery of a new genus recorded here suggests that the knowledge of the Mexican linyphiids is deficient in general, and particularly from habitats barely explored like the montane cloud forests.…”
Section: Discussionmentioning
confidence: 86%
“…Most of the Mexican species were described or recorded from the end of the 19 th century to the first half of the 20 th century (Banks 1898;Pickard-Cambridge 1902;Gertsch & Davis 1937, 1946 and later, only two publications by Millidge (1983Millidge ( , 1987 added another important number of species. Since then, only five species have been added to the Mexican Linyphiidae fauna (Ibarra-Núñez et al 2011;Prentice & Redak 2013;Gómez-Rodríguez et al 2014;Jiménez et al 2018;Campuzano Granados et al 2019). The discovery of a new genus recorded here suggests that the knowledge of the Mexican linyphiids is deficient in general, and particularly from habitats barely explored like the montane cloud forests.…”
Section: Discussionmentioning
confidence: 86%
“…2c-d, 4b Distribución conocida. CUBA (World Spider Catalog, 2020) y MÉXICO: Baja California Sur (Jiménez et al, 2018), Hidalgo (Martínez-Sánchez & Chamé-Vázquez, 2019), Jalisco (Durán-Barrón, 2004), Nuevo León (Exline & Levi, 1962) y San Luis Potosí (Exline & Levi, 1962;Álvarez-Padilla Laboratory, 2012).…”
Section: Ariamnes Mexicanusunclassified
“…While the flora of the region has been well documented (Riemann & Exequiel, 2007;Wiggins, 1980), only a tiny fraction of terrestrial arthropods containing ecologically crucial taxa have been thoroughly studied (Clark & Sankey, 1999;Due & Polis, 1986). For spiders, to date, there are about 414 described species for the whole Baja California peninsula (Jiménez et al, 2018), a number certainly due to increase with further studies (Hernández-Salgado et al, 2022). Furthermore, a trackanalysis found that the Baja California peninsula hosts 3 of 9 generalized tracks for Mexico based on agelenid spiders (Maya-Morales et al, 2018).…”
Section: Introductionmentioning
confidence: 99%